Dissecting plasmodesmata molecular composition by mass spectrometry-based proteomics - Bayer, Emmanuelle M.; Salmon, Magali S. (Frontiers in Plant Science, 2013)
In plants, the intercellular communication through the membranous channels called plasmodesmata (PD; singular plasmodesma) plays pivotal roles in the orchestration of development, defence responses and viral propagation. PD are dynamic structures embedded in the plant cell wall that are defined by specialised domains of the endoplasmic reticulum and the plasma membrane. PD structure and unique functions are guaranteed by their particular molecular composition. Yet, up to recent years and despite numerous approaches such as mutant screens, immunolocalisation or screening of random cDNAs, only few PD proteins had been conclusively identified and characterised. A clear breakthrough in the search of PD constituents came from mass-spectrometry-based proteomic approaches coupled with subcellular fractionation strategies. Due to their position, firmly anchored in the extracellular matrix, PD are notoriously difficult to isolate for biochemical analysis. Proteomic-based approaches have therefore first relied on the use of cell wall fractions containing embedded PD then on “free” PD fractions whereby PD membranes were released from the walls by enzymatic degradation. To discriminate between likely contaminants and PD protein candidates, bioinformatics tools have often been used in combination with proteomic approaches. GFP fusion proteins of selected candidates have confirmed the PD association of several protein families. Here we review the accomplishments and limitations of the proteomic based strategies to unravel the functional and structural complexity of PD. We also discuss the role of the identified PD associated proteins.